CFD Simulation of the Volvo Cars Slotted Walls Wind Tunnel - Olander, Mattias (My University, 2011)
When CFD simulations are performed at Volvo Cars, a case which resembles the condition for a car traveling on a open road is simulated. The results from these simulations have often proved to be different compared to the results from the experiments in the Volvo Cars slotted walls wind tunnel. To investigate the reason behind these differences a number of CFD simulations of the Volvo Cars wind tunnel have been performed. The simulations have been focused on three main cases, empty tunnel, tunnel with a simplified S60 and tunnel with a detailed S80. The results have been compared to ordinary CFD simulations and to newly made experiments in the wind tunnel. The flow produced by the numerical simulations in the empty wind tunnel has proved to be largely asymmetric due to the asymmetric geometry of the slotted walls’ support structure. This has greatly affected the flow around a car in the tunnel resulting in a different flow field compared to the standard CFD simulation. The drag and lift coefficient of the S60 and S80 have been lower in the CFD simulations of the wind tunnel compared to the ordinary CFD simulations, which is the opposite to what have been found when comparing the standard CFD simulations to the real experiments in the tunnel. The reason behind this is believed to be mainly due to the geometry simplifications of the simulated tunnel and the uniform inlet boundary condition, which have resulted in a very much more uniform flow in the CFD simulations compared to the experiments.
Keywords: Energi; Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig teknisk mekanik; Energy; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other engineering mechanics